In Vitro Synthesis of Proteins by Membrane-Bound Polyribosomes from Vesicular Stomatitis Virus-Infected HeLa Cells - Grubman, Marvin J. (1974)
Membrane-bound polysomes from vesicular stomatitis virus (VSV)-infected HeLa cells synthesize predominantly three proteins in an in vitro protein synthesizing system. These three proteins have different molecular weights than the viral structural proteins, i.e., 115,000, 88,000, and 72,000. Addition of preincubated L or HeLa cell S10 or HeLa cell crude initiation factors stimulates amino acid incorporation and, furthermore, alters the pattern of proteins synthesized. Stimulated membrane-bound polysomes synthesize predominantly viral protein G and lesser amounts of N, NS, and M. In vitro synthesized proteins G and N are very similar to virion proteins G and N based on analysis of tryptic methionine-labeled peptides. Most methionine-labeled tryptic peptides of virion G protein contain no carbohydrate moieties, since about 90% of sugar-labeled peptides co-chromatograph with only about 10% of methionine-labeled peptides. Sucrose gradient analysis of the labeled RNA present in VSV-infected membrane-bound polysomes reveals a relative enrichment in a class of viral RNA sedimenting slightly faster than the total population of the 13 to 15S mRNA, as compared to a VSV-infected crude cytoplasmic extract. A number of proteins, other than the viral structural proteins, are synthesized in the cytoplasm of five lines of VSV-infected cells. One of these proteins has the same molecular weight as the major in vitro synthesized protein, P(88). In vitro synthesized protein P(88) does not appear to be a precursor of viral structural proteins G, N, or M based on pulse-chase experiments and tryptic peptide mapping. Nonstimulated membrane-bound polysomes from uninfected HeLa cells synthesize the same size distribution of proteins as nonstimulated VSV-infected membrane-bound polysomes.